THE EFFICACY OF AZITHROMYCIN PLUS LEVAMISOLE VS AZITHROMYCIN ALONE IN THE TREATMENT OF MODERATE TO SEVERE ACNE - Waqas, Muhammad; Anwar, Ayesha; Ejaz, Amer; Malik, Anum (Journal of Ayub Medical College Abbottabad, 2021)
Background: Acne vulgaris (AV) is an inflammatory disorder of pilosebaceous unit and it affects over 85% of teenagers (peak age 17 years) during some point in their lives. Of these 30% have acne severe enough to require medical treatment. The overall incidence is comparable in both genders. Objective was to compare the efficacy of azithromycin plus levamisole with azithromycin alone in the treatment of moderate to severe acne. It was a single centre randomized controlled trial, conducted at the Department of Dermatology at Military Hospital Rawalpindi. Methods: We selected 118 patients of acne who fulfilled the inclusion criteria from the dermatology outpatient department. Diagnosis was based on clinical features of acne and severity defined using Acne Global Severity Score. The patients were randomly assigned two treatment groups; Patients in group A received Azithromycin 500 mg per day given for 3 days a week plus oral levamisole 150 mg per day was given for 2 days a week for a total of 08 weeks. Group B patients (N= 59) received Azithromycin 500 mg per day given for 3 days a week for a total of 08 weeks. Patients were followed up fortnightly till they completed their treatment. Response to treatment was graded according to the Acne Global Severity Score. Scoring was done at first visit before therapy and after 08 weeks of therapy in both groups. Therapy was considered efficacious if the patients achieved post-therapy reduction of global score below 19 at the end of 8th week of initiation of therapy.Results: Among our 118 study cases, we had 38 male patients while 80 were female patients. The study cases had mean age of 20.10±2.65 years. Mean global severity was 31.25±3.41 while 56 (47.5%) had moderate acne and 62 (52.5%) had severe acne. Efficacy was found to be higher in patients receiving Azithromycin plus levamisole combination. Conclusion: Azithromycin plus levamisole was observed as a more effective therapy for the treatment of acne as compared to Azithromycin alone. The study supports the administration of combination therapy for the treatment of Acne to achieve desired outcomes in patients.